Perinatal Mortality Associated with Positive Postmortem Cultures for Common Oral Flora - Mai He; Alison R. Migliori; Patricia Lauro; C. James Sung; Halit Pinar (Hindawi Limited, 2017)
Introduction. To investigate whether maternal oral flora might be involved in intrauterine infection and subsequent stillbirth or neonatal death and could therefore be detected in fetal and neonatal postmortem bacterial cultures. Methods. This retrospective study of postmortem examinations from 1/1/2000 to 12/31/2010 was searched for bacterial cultures positive for common oral flora from heart blood or lung tissue. Maternal age, gestational age, age at neonatal death, and placental and fetal/neonatal histopathological findings were collected. Results. During the study period 1197 postmortem examinations (861 stillbirths and 336 neonatal deaths) were performed in our hospital with gestational ages ranging from 13 to 40+ weeks. Cultures positive for oral flora were identified in 24 autopsies including 20 pure and 8 mixed growths (26/227, 11.5%), found in 16 stillbirths and 8 neonates. Microscopic examinations of these 16 stillbirths revealed 8 with features of infection and inflammation in fetus and placenta. The 7 neonatal deaths within 72 hours after birth grew 6 pure isolates and 1 mixed, and 6 correlated with fetal and placental inflammation. Conclusions. Pure isolates of oral flora with histological evidence of inflammation/infection in the placenta and fetus or infant suggest a strong association between maternal periodontal conditions and perinatal death.